Knowledge, Perceptions and Practices Regarding Menstrual Hygiene among Students - Jatal, Manika; Chaudhary, Neha (NPRC Journal of Multidisciplinary Research, 2024)
Menstrual hygiene management (MHM) is a critical aspect of public health, especially for adolescent students. This study investigates the knowledge, perceptions, and practices regarding menstrual hygiene among students. Menstrual hygiene is a critical aspect of health and well-being, yet it remains a taboo topic in many cultures, affecting the knowledge, perceptions, and practices of individuals, particularly students. This study aims to explore and analyze the knowledge, perceptions, and practices regarding menstrual hygiene among students. Through a comprehensive literature review and a structured survey, this research investigates the awareness levels, cultural and societal influences, and hygiene practices adopted by students during menstruation. The findings reveal significant gaps in knowledge, influenced by socio-cultural norms and educational disparities, which impact the perceptions and practices of menstrual hygiene. The study highlights the need for improved educational interventions and policy changes to promote better menstrual hygiene management, ensuring a healthier and more supportive environment for students. The implications of this research extend to public health policies, educational curricula, and community programs aimed at enhancing menstrual hygiene awareness and practices among the youth. Findings suggest that while there is a general awareness of menstrual hygiene, significant gaps persist in knowledge and practices, often exacerbated by cultural taboos and inadequate resources. The study highlights the need for comprehensive education programs and improved facilities to support menstrual health, ultimately advocating for policies that address these gaps to enhance the quality of life and educational outcomes for female.